2022
DOI: 10.3389/fsufs.2022.887311
|View full text |Cite
|
Sign up to set email alerts
|

The role of soaking, steaming, and dehulling on the nutritional quality of Bambara groundnuts (Vigna subterranea (L) Verdc.)

Abstract: Bambara groundnut (Vigna subterranea (L) Verdc.) is a leguminous plant that is widely cultivated in West Africa for its nutritious seeds. However, the hard-to-cook phenomenon of this legume affects its patronage by consumers. The quality and bioavailability of nutrients are affected by processing techniques during cooking. This study evaluated the effects of processing techniques on the nutritional quality of two Bambara groundnut varieties (namely, Simbi-bile and Sinkpili-zee). For this, each variety was subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This inevitably gives credence to the general supposition that most minerals are accumulated on the outer part of a grain and, as observed in this study, the process of dehulling reduces the levels of minerals, irrespective of the grain type. However, although not investigated in this study, a clear advantage of dehulling as reported in available literature is the reduction in antinutrient levels [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…This inevitably gives credence to the general supposition that most minerals are accumulated on the outer part of a grain and, as observed in this study, the process of dehulling reduces the levels of minerals, irrespective of the grain type. However, although not investigated in this study, a clear advantage of dehulling as reported in available literature is the reduction in antinutrient levels [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Soaking and roasting among other traditional processing methods, have been employed to enhance the nutritional content of cereals and pulses (Chauhan et al, 2022). Specifically, soaking is commonly used as a preliminary treatment for legumes prior to processing (Yahaya et al, 2022). Toasting/ roasting, a prevalent dry heat processing technique, serves various purposes, inducing notable alterations in moisture content, appearance, texture, etc.…”
mentioning
confidence: 99%